EFISIENSI TATANIAGA EKSPOR BIJI TENGKAWANG DARI KALIMANTAN BARAT - Satria Astana; Subandi Antaatmaja; Rachman Effendi; Buharman Buharman (Jurnal Penelitian Hasil Hutan, 1987)
Efficiency  of marketing  system has an important  role in supply and demand  balance.  It could be indicated by the marketing margin. A lower marketing  margin  would  mean  lower prices  to consumers, higher prices  to producers,  and a greater quantity  of  the good  exchange.The marketing system for illipe-nuts export from West Kalimantan has two main channels,  intermediate  sellers and exporters. The price spread analysis reveals that the marketing system  mechanism  is inefficient. The farmer margin is 45.83%  and  the marketing  margin is 54.17%  of the export price. The marketing margin consists of 32.27% of profit (and risk) margin and 21.90% of marketing  cost.  The biggest marketing cost is on the intermediate  seller (12.50%). However,  the highest margin for  profit  (and risk) is on the exporter  (19.76%);   the margin for  profit  (and risk) for  the intermediate  seller is 12.5%  and  the marketing  cost for the exporter  is 9.40%..In the marketing system, the farmer's earning is 17.01% of  the production cost  when poor  harvest; the production cost  is Rp. 64276.38 includes 58.41% of accomodation costs, 35.99%  of transportation   costs and 5.60%  of  tool  costs. In the rich harvest,  the farmer's earning  is estimated  at 30.0%  of the production  cost under the assumption  that the decreasing of the price due to the production   increases is about  18%. If inefficiency of  the marketing  system  can be overcomed, the farmer's earning both  in the poor and rich harvests  will be able to increase.